Understanding the protective ability of the native oxide on an Fe-13 at% Cr alloy at the atomic scale: A combined atom probe and electron microscopy study. (February 2023) - Sasidhar, K.N.; Khanchandani, Heena; Zhang, Siyuan; da Silva, Alisson Kwiatkowski; Scheu, C.; Gault, Baptiste; Ponge, Dirk; Raabe, Dierk
Abstract: We have performed high-resolution structural and chemical characterization of the native oxide films formed on a ferritic Fe- 13 at% Cr alloy at different stages of growth. The steady-state protective oxide film was found to be 5–6 nm thick, epitaxially grown, with a cubic spinel-structure ((Fe, Cr)3 O4 ) and a Baker-Nutting orientation-relationship with the underlying alloy. Composition evolution within the oxide during growth, measured by atom probe tomography, has been explained on the basis of the low solid-state mobility of Cr 3+ cations. We propose that the miscibility gap in the Fe-Cr spinel oxide solid-solution can be used to explain the reduced driving force for oxide-layer thickening with time. Highlights: Near-atomic scale characterization of native oxide film on ferritic stainless steel. Epitaxial spinel-structured (Fe, Cr)3 O4 film with Baker-Nutting OR. Cr-enrichment in oxide film results from low Cr 3+ cation diffusivity. Miscibility gap in Fe-Cr spinel oxide contributes to its protective ability.